ANALISIS PERILAKU PENCEGAHAN DEMAM BERDARAH DENGUE: STUDI LITERATURE - dony setiawan hendyca putra; Hela Denia Pratiwi; Hendro Prasetyo; Akhmad Efrizal Amrullah (Politeknik Unggulan Kalimantan, 2022)
Dengue Hemorrhagic Fever (DHF) is one of the main public health problems in Indonesia. The number of sufferers and the area of Dengue Hemorrhagic Fever (DHF) spread is increasing along with the increasing mobility, environment, climate, population density and community behavior, especially in tropical and sub-tropical areas. Methods: The search strategy used by researchers in making this Literature Review was to use the keyword